George W. Bush's and Barack H. Obama's foreign policies toward Ghana : a comparative analysis - Iddris, Abdul Razak, 1964- (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2018)
Using a mixture of qualitative and quantitative analytical techniques, this book offers a comparative analysis of the policies of Presidents George W. Bush and Barack H. Obama towards Ghana. The focus is on their economic aid, military aid, and immigration policy instruments.